Strategi Mengatasi Tantangan Kurangnya Minat Berorganisasi dalam Mengaktualisasikan Nilai Pancasila pada Mahasiswa Universitas Bandar Lampung - Putri Febriana Wulandari (Lembaga Pengembangan Kinerja Dosen, 2025)
The declining interest of students in joining organizations poses a challenge in character development and strengthening Pancasila values in higher education institutions. This study aims to investigate the causes of low student involvement in student organizations and to design strategies for strengthening the implementation of Pancasila values through organizational activities. A qualitative method is applied in this research through in-depth interviews with administrators, active members, and students with organizational experience. The data is then analyzed based on Albert Bandura's Social Learning Theory to understand the social learning process as a shaper of student behavior. The research findings reveal that the low interest in organizing is caused by several factors, namely lack of institutional support, limited facilities, and minimal recognition for active students. Nevertheless, the role of student organizations is crucial in fostering discipline, a sense of responsibility, cooperation, and the spirit of deliberation that reflects Pancasila values. Strengthening efforts can be carried out through improved institutional development, providing awards to active students, and implementing organizational programs based on national values and Pancasila character.